Policy Implications of The Indonesia Smart Program for Senior High Schools (SMA/SMK) at The Education Office of Nabire Regency - Hasriati Mesalangi; Baharuddin Baharuddin; Yoel Pasae (Jurnal Indonesia Sosial Teknologi, 2025)
This research establishes the research object at the Education Office of Nabire Regency, focusing on the Policy of the Indonesia Smart Program at the SMA/SMK level. This study aims to understand and analyze the Implications of the Indonesia Smart Program Policy at the SMA/SMK level in the Education Office of Nabire Regency. This type of research employs a qualitative approach. The results of this research indicate that the implementation of the Indonesia Smart Program (PIP) in Nabire Regency exhibits a strong correlation with government policies aimed at improving access to and the quality of education. The positive impacts observed from the implementation of the Indonesia Smart Program (PIP) in Nabire Regency include improved access to education, increased family welfare, and enhanced community awareness. Meanwhile, the challenges faced include delays in fund disbursement, a lack of community understanding, inadequate infrastructure, and the potential for fund misuse. The Indonesia Smart Program (PIP) has made significant contributions to student participation at the SMA/SMK level by alleviating the financial burden of education for students from underprivileged families. The Indonesia Smart Program (PIP) is a strategic step towards creating more equitable and fair educational opportunities, contributing to human resource development, particularly for school-age students in Nabire Regency.